2017
DOI: 10.17796/1053-4628-41.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotic Yogurt and Xylitol-Containing Chewing Gums on Salivary S Mutans Count

Abstract: Probiotic yogurt and xylitol-containing chewing gums seem to be as effective in reduction of salivary S. mutans levels. Their constant long-term consumption is thus recommended to prevent caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
1
20
0
2
Order By: Relevance
“…Xylitol cannot be fermented by oral microorganisms and has been shown to reduce S. mutans levels in plaque and saliva and markedly reduce tooth decay. The antibacterial effect of xylitol have been evaluated by various studies [95,96], but the amount added to the materials may change the efficacy. According to a study, it was found that it did not show any antibacterial effect under a certain level [97].…”
Section: Discussionmentioning
confidence: 99%
“…Xylitol cannot be fermented by oral microorganisms and has been shown to reduce S. mutans levels in plaque and saliva and markedly reduce tooth decay. The antibacterial effect of xylitol have been evaluated by various studies [95,96], but the amount added to the materials may change the efficacy. According to a study, it was found that it did not show any antibacterial effect under a certain level [97].…”
Section: Discussionmentioning
confidence: 99%
“…As we are experienced and also the cheapest and the simplest standardized method for our laboratory capabilities, the conventional quantitative culture techniques are preferred in this study. This microbiological method have been used in some recent researches happening in dentistry and also different fields (Vale et al, 2014; Relvas et al, 2014; Gupta and Gupta, 2015; Ghasemi et al, 2017; Salman et al, 2017). Although it is an old method, it still maintains its reliability and validity.…”
Section: Discussionmentioning
confidence: 99%
“…Very important factor is the use of different means of delivery such as dairy products, chewing gums and drops to transfer probiotics. The probiotic channels of supply are suitable for all ages, especially for young children [27]. In present study the yogurt is selected because it is safe, available and used routinely in Serbian children's diet.…”
Section: Discussionmentioning
confidence: 99%